Cognitive and Behavioral Differences Between Subtypes in Refractory Irritable Bowel Syndrome. Issue 3 (May 2019) - Windgassen, Sula; Moss-Morris, Rona; Everitt, Hazel; Sibelli, Alice; Goldsmith, Kimberley; Chalder, Trudie
Abstract: Irritable bowel syndrome (IBS) is a functional gastrointestinal syndrome consisting of different bowel pattern subtypes: diarrhea predominant (IBS-D), constipation predominant (IBS-C), and alternating (IBS-A). This paper aimed to identify whether (a) psychological factors implicated in the cognitive behavioral model of IBS were differentially associated with bowel pattern subtypes, (b) whether there were differences in symptom severity and work and social adjustment across the IBS-subtypes. Analysis was conducted on baseline data of 557 individuals with refractory IBS recruited into the Assessing Cognitive Therapy in Irritable Bowel (ACTIB) randomized controlled trial. Correlations assessed the associations between psychological factors, stool patterns, symptom severity, and work and social adjustment. Hierarchical regressions identified whether cognitive and behavioral factors were significantly associated with frequency of loose/watery stools, hard/lumpy stools and symptom severity while controlling for affective (anxiety and depression) and demographic factors (age, gender, symptom duration). One-way ANOVAs were conducted to assess differences across Rome III classified subtypes (IBS-A, D and C) in cognitive, behavioral, affective, symptom severity, and adjustment measures. Psychological factors were significantly associated with symptom severity and work and social adjustment. Increased avoidance behavior and unhelpful gastrointestinal (GI) cognitions were significantly associated with higher frequency of loose/watery stools. Increased control behaviors were associated with higher frequency of hard/lumpy stools. Cognitive and behavioral differences were significant across the Rome III classified IBS subtypes. There were no differences in anxiety, depression, overall symptom severity, or work and social adjustment. The results are discussed in terms of their utility in tailoring cognitive behavioral treatments to IBS subtypes. Highlights: Behavioral responses to symptoms are different across the IBS subtypes Avoidance behaviors are higher in diarrhea-predominant IBS Control behaviors are higher in constipation-predominant IBS Those with alternating IBS engage in both avoidance and control behaviors Gastrointestinal-related cognitions are higher in diarrhea-predominant IBS